Close genetic relationship between central Thai and Mon people in Thailand revealed by autosomal microsatellites - Suparat Srithawong (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Central Thailand is home to diverse populations with the central Thai constituting the major group, while the Mon, who migrated from southern Myanmar, are sparsely distributed within the region. A total of 338 individuals of eight central Thai (246 samples) and three Mon populations (92 samples) were newly genotyped. When combined with our previously published Mon data, this provides a total of 139 Mon samples. We found genetic similarity between the central Thai and Mon and weak sub-structuring among Thais from central, northern, and northeastern Thailand. The forensic parameter results show high discrimination values which are appropriate for forensic personal identification and paternity testing in both the central Thai and Mon; the probabilities of excluding paternity are 0.999999112 and 0.999999031, respectively, and the combined discrimination power is 0.9999999999999999999999 in both groups. This regional allelic frequency on forensic microsatellites may serve as a useful reference for further forensic investigations in both Thailand and Myanmar.